Decrease of Cardiac Parkin Protein in Obese Mice - Thomas, Amandine; Marek-Iannucci, Stefanie; Tucker, Kyle C.; Andres, Allen M.; Gottlieb, Roberta A. (Frontiers in Cardiovascular Medicine, 2020)
Mitophagy plays a major role in heart physiology. Impairment of Parkin-dependent mitophagy in heart is known to be deleterious. Obesity is a known cardiovascular risk factor. Impaired autophagy has been reported in models of obesity or hyperlipidemia/hypercholesterolemia; however less is known regarding obesity and mitophagy. The aim of this study was to evaluate the regulation of Parkin expression in hearts of mice fed a high fat diet. Interestingly, we found a significant decrease in Parkin protein in hearts of HFD mice compared those fed a low-fat diet. However, this downregulation was not associated with a decrease in Parkin mRNA expression. We did not detect any change in the degradation rate of Parkin and only a slight decrease in its translation. The reduction of Parkin protein abundance in HFD hearts remains a mystery and will need further studies; however, depletion of Parkin in the setting of obesity may contribute to cardiovascular risk.